Chemical Probes and Activity-Based Protein Profiling for Cancer Research - Al Mazid, Mohammad Faysal; Park, Seung Bin; Cheekatla, Subba Rao; Murale, Dhiraj P.; Shin, Kyung Ho; Lee, Jun-Seok (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Chemical probes can be used to understand the complex biological nature of diseases. Due to the diversity of cancer types and dynamic regulatory pathways involved in the disease, there is a need to identify signaling pathways and associated proteins or enzymes that are traceable or detectable in tests for cancer diagnosis and treatment. Currently, fluorogenic chemical probes are widely used to detect cancer-associated proteins and their binding partners. These probes are also applicable in photodynamic therapy to determine drug efficacy and monitor regulating factors. In this review, we discuss the synthesis of chemical probes for different cancer types from 2016 to the present time and their application in monitoring the activity of transferases, hydrolases, deacetylases, oxidoreductases, and immune cells. Moreover, we elaborate on their potential roles in photodynamic therapy.